Pengaruh Faktor Pribadi dan Sosial Terhadap Keputusan Anggota Memilih BMT NU Ngasem Cabang Kapas Sebagai Pembiayaan - Kiki Fitrian Wulandari; Moch Khoirul Anwar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of personal and social factors on members' decisions to choose BMT NU Ngasem Kapas Branch as funding. The research method applied is through a quantitative approach, by collecting primary data through distributing questionnaires in the form of Google from. Samples were taken using the probability sampling method with the criteria of financing members at BMT NU Ngasem Kapas Branch. The results of research using the SPSS program show that in hypothesis testing, namely partial and simultaneous tests, personal and social factors have a significant influence on members' decisions in choosing BMT NU Ngasem Kapas Branch as funding. The existence of personal factors and social factors strengthens members' decisions in choosing BMT NU Ngasem as funding.